Optimization of competitive selection models of applicants - T. V. Kisel (Системный анализ и прикладная информатика)
The subject of research is the use of blockchain technology in IT medicine. The purpose of the article is to analyze the use of blockchain technology in IT medicine, analyze its use in the world, and propose models: the directions of blockchain in medicine and electronic marketing. The main directions of using blockchain technology in medicine are considered, the application and prospects of using blockchain in medical institutions of Russia and developed countries of the world are determined. The analysis of various projects is carried out. Blockchain technologies allow you to transfer work to a digital medium, digitize all data and work with all documents within a large global information system. Advantages: decentralization, personal ownership of medical data, accessibility and reliability, transparency and trust, verifi of data. A model of information management in IT medicine using blockchain has been developed, including the management of electronic medical records; drug supply chain management and anti-counterfeiting; analysis of medical data; conducting clinical and biomedical research; remote monitoring of patients. The structure of Internet marketing has been developed on the basis of a distributed system using a portal of subsystems for the supply and distribution of medicines to meet the needs of patients for various medical institutions of the Republic of Belarus, with the support of intelligent agents and blockchain technologies.